Investigation of structure, mechanical properties, and electrical conductivity of LixCo(1-x)O2: Validation using a nanoquantum model - Obaidallah A. Algethami (Next Materials)
Nanoquantum models are built in order to advance nanotechnology by adapting classical laws to quantum principles using string theory. In this study, a theoretical model based on string theory is proposed to meld — and then extract — mechanical and electrical properties that recognize the particle-wave duality inherent in Quantum laws. Experimentally, lithium cobalt oxide (LixCo(1-x)O2; x = 0.1, 0.3, 0.5, 0.7, and 0.9) nanoparticles were synthesized by the sol-gel method. X-ray diffraction analysis revealed the hexagonal crystal structure (R-3m space group). It has been shown that reducing the lithium concentration results in greater dislocation density, internal stress, strain, and smaller nanocrystal size. Electrical measurements exhibit semiconducting behavior, with increasing conductivity as a function of temperature and lithium concentration. Improved conductivity is inherently tied to storage capacity and so offers the potential to improve lithium-ion battery performance. Infrared analysis shows that Li-Co bonds exist at wavenumbers of approximately 600 and 900 cm⁻¹ and Co bonds at about 1080 and 1580 cm⁻¹ . The quantum model agrees well with the measured electrical and mechanical properties and provides a new framework for acceleration nanotechnology research. The results indicate a systematic approach to enhancing nanomaterials for energy storage and other applications.